Experiment of PI Controller for Indirect Current Control for Single – Phase Shunt Active Filter - Yodmanee, Kanapot; Sriprang, Songklod; Katwattanakul, Anurak; Noosawang, Sakrit; Lenwari, Wanchak (Engineering and Technology Horizons, 2024)
Due to harmonic problems caused by various factors that resulted in damages and malfunctions of electrical equipment in the power system, eliminating harmonics in the electrical system has become an important issue for both industrial and household sectors. This article focuses on developing a current control method for a single-phase shunt active power filter (APF) that controls current by an indirect method. The detection of load current to generate reference signals uses the dq-axis reference frame for a single-phase electrical system. The design of circuit parameters and PI controller parameters for compensating current and DC bus voltage are based on a simple calculation method. Simulation and experimental results confirm that the proposed current control method and PI controller design effectively eliminate harmonics, with the percent of total current harmonic distortion (THDi) values of the supply current after compensation within the IEEE Std 519-2022 standard limit.